Mechanical and thermal properties of graphene sulfonate nanosheet reinforced sacrificial concrete at elevated temperatures. (30th October 2017) - Chu, Hong-yan; Jiang, Jin-yang; Sun, Wei; Zhang, Mingzhong
Graphical abstract: Highlights: New test setups for mechanical properties measurement at high temperatures are presented. Microstructure of sacrificial concrete is improved due to the incorporation of GSNSs. Compressive strength of sacrificial concrete increases by 12.98–25.36%. Splitting tensile strength of sacrificial concrete increases by 8.66–34.38%. Thermal diffusivity of sacrificial concrete rises by 25.00–103.23%. Abstract: Progress in the field of nanomaterials presents an opportunity to improve the performance of cementitious composites via graphene or its derivatives. This paper presents an experimental study on mechanical and thermal properties of sacrificial concrete without and with graphene sulfonate nanosheets (GSNSs) during high temperature exposure. The microstructure, porosity, mechanical strengths, thermal analysis, coefficient of thermal expansion, thermal diffusivity and ablation behaviour of sacrificial concrete during exposure to various temperatures up to 1000 °C were comprehensively investigated. Two new experimental apparatuses were developed and used to measure mechanical strengths of sacrificial concrete at elevated temperatures. It was found that the compressive strength, splitting tensile strength, thermal diffusivity and decomposition enthalpy of sacrificial concrete were increased by 12.98–25.36%, 8.66–34.38%, 25.00–103.23% and 4.23% respectively when adding 0.1 wt% GSNSs, while the porosity and ablation velocity of sacrificial concrete were reduced by 3.01–6.99% and 4.14% respectively due to the incorporation of GSNSs.